Factors Affecting Telang (Clitoria ternatea L.) Germination: Systematic Literature Review - Kuswantoro, Farid; Li'aini, Arrohmatus Syafaqoh (Universitas Panji Sakti, 2024)
Clitoria ternatea is a multipurpose plant species. Interest in this plant species has increased recently as its antioxidant properties made it a popular natural food additive. This condition implies that a review study to understand the current development of C. ternatea germination biology, especially factors affecting its germination, is essential to help interested stakeholders cope with future demand. Thus, this study aims to use a systematic literature method to provide data on factors affecting C. ternatea germination. Data on this topic is acquired from the publication in the Google Scholar database. The publications were screened to acquire relevant publications for the review process. This study found that dormancy, pod maturity and seed age are internal factors affecting C. ternatea germination. Meanwhile, external factors such as dormancy alleviation, hormone and PGPR treatment, allelopathic compound, storage, and germination conditions such as storage and substrate temperature also affect the plant species' germination. In conclusion, based on the provided data, C. ternatea germination, like the germination of any other plant species, is affected by internal and external factors.